PSYCHOLINGUISTIC EXPRESSION OF NATIONALITY IN MIMEMIC TEXTS (International journal of artificial intelligence, 2026)
This article examines the issue of the psycholinguistic expression of national identity in mimemic texts. The study analyzes the close relationship between facial expressions and gestures and nationally shaped perceptions, emotional states, and psychological stereotypes formed in human consciousness. The role of mimemic units in the speech process and their functional characteristics in expressing national mentality within communicative situations are discussed based on a psycholinguistic approach. The article substantiates mimemic texts as an important nonverbal means of expressing national consciousness and cultural identity and demonstrates their significance in revealing the relationships between language, thought, and culture.